Edukasi Mitigasi Bencana dalam Membentuk Sikap Siaga Bencana pada Siswa SDN Koncer 2 Kabupaten Bondowoso - Dero Maulana Imani; Aulia Rahma Putri; Muhammad Rafly Armada; Tia Milinda Rastiningsih; Luluk Faizah; Delis Ning Agustina; Nova Shufia Tahmida; Agung Nugroho Puspito (Jurnal Pengabdian Nasional (JPN) Indonesia, 2026)
Indonesia has a high level of disaster vulnerability, yet the understanding of disaster mitigation and preparedness among elementary school students, particularly at SDN Koncer 2 Bondowoso Regency, remains low. This study aims to foster disaster preparedness among fourth and fifth grade students through a participatory approach. The implementation method was conducted in April 2026 involving 20 students from grades IV and V through preparation, interactive socialization and simulation, and evaluation using pre-test and post-test instruments. The results indicate a significant increase in student understanding, with average scores rising from 32.5 in the pre-test to 75.4 in the post-test. The use of learning media such as volcanic eruption, flood, and landslide simulations proved effective in increasing enthusiasm and students' independent evacuation skills. In conclusion, disaster mitigation education using participatory methods and simulations successfully developed disaster-responsive character and improved students' preparedness for emergency conditions at school and in daily life.